A legal framework for international supervision : the EEC model - Muller, H.J. (Amsterdam De Nederlandsche Bank, 1984)
The title of this article indicates the quest of the national authorities to achieve harmonization of the present forms of supervision, with the international aspect playing a role in those cases where, as a result of the implementation of the principle of consolidation, supervision transcends the national borders
This article appeared in: Issues in Banking Regulation, Vol. 8, No. 1 Summer 1984), pp. 36 - 42
osc 30/01/2019
Loans
Keywords: Bank regulation